Quantitative proteomics reveals reduction of endocytic machinery components in gliomasResearch in context - Dominik P. Buser (EBioMedicine, 2019)
Background: Gliomas are the most frequent and aggressive malignancies of the central nervous system. Decades of molecular analyses have demonstrated that gliomas accumulate genetic alterations that culminate in enhanced activity of receptor tyrosine kinases and downstream mediators. While the genetic alterations, like gene amplification or loss, have been well characterized, little information exists about changes in the proteome of gliomas of different grades. Methods: We performed unbiased quantitative proteomics of human glioma biopsies by mass spectrometry followed by bioinformatic analysis. Findings: Various pathways were found to be up- or downregulated. In particular, endocytosis as pathway was affected by a vast and concomitant reduction of multiple machinery components involved in initiation, formation, and scission of endocytic carriers. Both clathrin-dependent and -independent endocytosis were changed, since not only clathrin, AP-2 adaptins, and endophilins were downregulated, but also dynamin that is shared by both pathways. The reduction of endocytic machinery components caused increased receptor cell surface levels, a prominent phenotype of defective endocytosis. Analysis of additional biopsies revealed that depletion of endocytic machinery components was a common trait of various glioma grades and subclasses. Interpretation: We propose that impaired endocytosis creates a selective advantage in glioma tumor progression due to prolonged receptor tyrosine kinase signaling from the cell surface. Fund: This work was supported by Grants 316030-164105 (to P. Jenö), 31003A-162643 (to M. Spiess) and PP00P3-176974 (to G. Hutter) from the Swiss National Science Foundation. Further funding was received by the Department of Surgery from the University Hospital Basel. Keywords: Glioma, Endocytosis, RTK, Dynamin, Clathrin, AP-2